Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea - Huang, Mian; Huang, Yong; Xu, Kuidong (Zootaxa, 2019)
A new species of the genus Thalassironus de Man, 1889, which was discovered from marine sediments in the South China Sea, is described here as Thalassironus filiformis sp. nov. The new species is characterized by having short outer labial setae and cephalic setae of equal length, long filiform tail, buccal cavity with three anterior teeth and three additional teeth just posterior to amphideal fovea, male with a segmented midventral precloacal seta, spicules double curved, slender with ventral ala. It is very similar to Thalassironus lynnae Keppner, 1987, but can be differentiated from the latter species by much shorter cephalic setae (8 μm vs 14–16 μm), longer tail (772–780 μm vs 300–506 μm), longer spicules (67–68 μm vs 35–40 μm), smaller value of de Man ratio “a” (66 vs 99.7–102) and different structure of spicules. An updated dichotomous key to all known species of Thalassironus is provided.